Nutrigenomics and nutrigenetics in functional foods and personalized nutrition - Ferguson, Lynnette R (CRC Press, 2014)
While functional foods have become a reasonably well-established concept, personalized nutrition is still treated with skepticism by many. The recognition that people would have different nutrient requirements, or perceive foods in different ways, raises several concerns-some real, some not so real. Nutrigenomics and Nutrigenetics in Functional Foods and Personalized Nutrition addresses what is needed to bring nutrigenomics, nutrigenetics, and their associated technologies to market in a truly impactful way. Edited by Lynnette R. Ferguson, a well-known and internationally respected researcher.